Update on Existing and Upcoming Branched and Fenestrated Thoracic Aortic Arch Stent Grafts - Brescia, Alexander A.; Wanken, Zachary J.; Ohman, J. Westley; Kachroo, Puja; On Behalf of the Washington University Collaborative for Aortic Research (WashU-CAR) (Seminars in Interventional Radiology, 2024)
Conventional management of thoracic aortic arch aneurysm and dissection with aneurysmal degeneration remains open surgical repair. However, multiple branched and fenestrated endograft systems offer promise for hybrid or total endovascular treatment of aortic arch pathology. Two zone 0 solutions involving an aortic arch with innominate branch and ascending aorta components are contemporarily in trial: the Gore thoracic branch endoprosthesis and ascending stent graft in the ARISE II Trial (W. L. Gore & Associates, Newark, Delaware) and the NEXUS Arch Stent Graft System (Endospan Ltd., Herzliya, Israel). Both device systems require a debranching procedure prior to endovascular treatment. Patients deemed appropriate for endovascular treatment with acute pathology or not qualifying for one of these trial devices may undergo homemade single or multiple fenestrated physician-modified endovascular grafts or in situ laser fenestration of aortic arch grafts with branch stenting to treat arch pathology. Ultimately, a durable total endovascular solution must achieve comparable or superior outcomes compared with open surgical repair, at significantly lower impact to patients. Branched and fenestrated endovascular treatments for aortic arch pathology require further investigation and follow-up to determine early, mid, and long-term outcomes including mortality, stroke, and endoleak requiring reintervention.
Keywords: aortic arch; aortic dissection; aortic aneurysm; TEVAR; stent graft; interventional radiology